Cultural Muslims: Background Forces and Factors Influencing Everyday Religiosity of Muslim People - YILMAZ, Selman (Journal of History Culture and Art Research, 2014)
Cultural Muslims: Background Forces and Factors Influencing Everyday Religiosity of Muslim People Abstract Most observers of the science of religion define Islam as a monolithic religion. Some people pinpoint a cultural practice from a Muslim-majority country and generalize it as a practice of all Muslims around the world by assuming that Islam is a monolithic religion. In fact, Islam never meant the same thing to all Muslims. While the majority of Muslims agree on the core tenets of Islam, Muslims across the world differ significantly in their levels of religious commitment and openness to multiple interpretations of their faith. In addition, fluctuation on the core tenets of Islam among Muslim majority countries suggest that some Muslims make religion a part of their cultural life and practice religion as a cultural habit. There are many points that cultural and religious practices are mixed. This study helps to acknowledge the relationship between regional culture and religious culture, and background reasons of common everyday activities of Muslim people.